Hundred-Joule-level, nanosecond-pulse Nd:glass laser system with high spatiotemporal beam quality. (22nd March 2016) - Li, Sensen; Wang, Yulei; Lu, Zhiwei; Ding, Lei; Chen, Yi; Du, Pengyuan; Ba, Dexin; Zheng, Zhenxing; Wang, Xin; Yuan, Hang; Zhu, Chengyu; He, Weiming; et al.
Abstract : A 100-J-level Nd:glass laser system in nanosecond-scale pulse width has been constructed to perform as a standard source of high-fluence-laser science experiments. The laser system, operating with typical pulse durations of 3–5 ns and beam diameter 60 mm, employs a sequence of successive rod amplifiers to achieve 100-J-level energy at 1053 nm at 3 ns. The frequency conversion can provide energy of 50-J level at 351 nm. In addition to the high stability of the energy output, the most valuable of the laser system is the high spatiotemporal beam quality of the output, which contains the uniform square pulse waveform, the uniform flat-top spatial fluence distribution and the uniform flat-top wavefront.